The Role of the Patients' Companion in the Transitional Care from the Open Heart Surgery ICU to the Cardiac Surgery Ward A Qualitative Content Analysis - Khoshkesht, Sahar (International journal of community based nursing and midwifery, 2021)
Copyright: © International Journal of Community Based Nursing and Midwifery.